Motivation and responsibility of employees of primary health care facilities: results of a social survey on current motivation measures - O. M. Drapkina; A. Sh. Senenko; R. N. Shepel (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the relevance of motivation measures based on the survey of medical staff.Material and methods. Medical staff of adult primary health care facilities was surveyed using an original questionnaire regarding the organization of work, the importance of financial and non-financial incentives. The survey was strictly voluntary and anonymous, and conducted electronically and on paper. In total, 35191 questionnaires were accepted for processing. Processing was carried out using the method of descriptive statistics.Results. The organization of work environment is of the greatest importance to respondents (>80%), while in second place is the presence of clear criteria for work efficiency assessment, and in third place — a clear incentive and penal scheme. Respondents rated the opportunity for contact with the administration more highly than "communicating work assessment criteria to employees". The undisputed top in financial incentives is payments for high performance criteria in all categories of personnel. Of the non-financial measures, the most popular were a letter of gratitude from the manager and permission to independently plan working hours (maximum among medical specialists (51%)).Conclusion. The results obtained make it possible to highlight the main directions for motivation system of medical staff as follows: clear evaluation criteria for all personnel categories, provision of conditions for fulfilling the developed criteria, active outreach on evaluation criteria, incentive payments and other measures of material incentives, development of targeted incentive technologies, feedback with employees on issues related to their performance, working conditions, etc., developing a system of non-financial incentives and corporate culture.